The Geometry of Limb Motor Innervation is Controlled by the Dorsal–Ventral Compartment Boundary in the Chick Limbless Mutant. (1st December 2020) - Luria, Victor; Laufer, Ed
Highlights: The geometry of limb motor innervation is controlled by the dorsal–ventral compartment boundary. In chick limbless FGF-rescued limbs, the angle between dorsal and ventral nerves is large, changing motor nerve geometry. The dorsal–ventral motor axon targeting is not affected in rescued limbless limbs. The double-dorsal transformation of rescued limbless limbs is extensive but incomplete, and varies with time. Ventral V3 spinal interneurons are expanded in limbless, hinting at the molecular nature of the unidentified limbless gene. Abstract: Precise control of limb muscles, and ultimately of limb movement, requires accurate motor innervation. Motor innervation of the vertebrate limb is established by sequential selection of trajectories at successive decision points. Motor axons of the lateral motor column (LMC) segregate at the base of the limb into two groups that execute a choice between dorsal and ventral tissue: medial LMC axons innervate the ventral limb, whereas lateral LMC axons innervate the dorsal limb. We investigated how LMC axons are targeted to the limb using the chick mutant limbless (ll), which has a dorsal transformation of the ventral limb mesenchyme. In ll the spatial pattern of motor projections to the limb is abnormal while their targeting is normal. While extensive, the dorsal transformation of the ll ventral limb mesenchyme is incomplete whereas the generation, specification and targeting of spinal motor neurons are apparently unaffected. Thus, the dorsal–ventral motor axon segregation is an active choice that is independent of the ratio between dorsal and ventral tissue but dependent on the presence of both tissues. Therefore, the fidelity of the motor projections to the limb depends on the presence of both dorsal and ventral compartments, while the geometry of motor projections is controlled by the position of limb dorsal–ventral compartment boundary.